A Comparative Analysis of the Performance of Sharia and Conventional Equity Mutual Funds in Indonesia: A Review of Reputation, Stock Selection, and Market Timing - Kavi Sulaiman; R. Melda Maesarach (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the comparative performance of Sharia and conventional equity mutual funds in Indonesia by assessing the influence of reputation, stock selection ability, and market timing on risk-adjusted returns as measured by the Sharpe Ratio. The research is motivated by the increasing demand for Sharia-compliant investment alternatives and the growing competition with conventional financial products. The core problem addressed in this study is whether managerial strategies and reputation significantly differentiate the performance of Sharia-based funds from their conventional counterparts. The primary objectives are to analyze the effects of fund reputation, stock selection skills, and market timing on mutual fund performance and to identify whether significant differences exist between Sharia and conventional funds. This quantitative study employs a comparative and causal associative approach using secondary data from 18 mutual funds (9 Sharia and 9 conventional) over the period 2020–2024. The Sharpe Ratio was calculated to measure performance, while stock selection and market timing abilities were evaluated using the Treynor-Mazuy model. The findings reveal that conventional mutual funds outperform Sharia mutual funds in terms of risk-adjusted return. However, no statistically significant differences were observed in stock selection and market timing abilities between the two fund types. Moreover, fund reputation did not significantly influence performance in either category. These results suggest that external market factors and strategic alignment may have a greater impact than past ratings or technical timing. The study contributes to both academic and practical investment discourse, offering insights for investors and fund managers seeking to optimize performance within ethical and financial constraints.